Beach house rules : a novel - Harvey, Kristy Woodson (Gallery Books, 2025)
"When Charlotte Sitterly's husband is arrested for a white-collar crime, she and her daughter Iris are locked out of their house by the FBI and--what's potentially even worse--thrust into the spotlight of @JuniperShoresSocialite, the town's snarky anonymous Instagram account. Cut off from her bank accounts and feeling desperate, Charlotte takes up an acquaintance's offer to stay at a beachfront former bed-and-breakfast that's home to a community of single mothers and draws plenty of gossip in the small coastal North Carolina town. Charlotte and Iris find solace and are surprised by how much fun they're having with the other families despite their circumstances. But when the women discover a secret link between them, it changes everything they thought they knew about the unconventional family they've created and leaves them wondering whether their coming together was a coincidence at all. Will the skeletons in the mommune closets help Charlotte and Iris reclaim their place in the Juniper Shores community--or shatter the sisterhood forever?"--